Teaching seasons with hands-on models: model transformation - Türk, Cumhur; Kalkan, Hüseyin (Research in science & technological education, 2018)
The purpose of this study was to examine the effects of using 'hands-on' models (HOMs) to teach the subject of seasons - a topic about which students often have misconceptions - on students' expressed models. To this end, three different HOMs were developed. The study sample consisted of 80 seventh graders (ages 12-13). The study had a quasi-experimental design, and a model with a control group was used. The experimental group and the control group were assigned randomly. The study data were collected using an open-ended question form that was administered three times: pre-instruction, post-instruction and a long time after instruction (permanence). The collected data were analysed using the content analysis technique. Frequencies and percentages were used to analyse the changes in the students' expressed models. The results of the analyses showed that using HOMs was an effective method for teaching the subject of seasons. It was concluded that whereas teaching with HOMs led the students to a 'scientific' model, the teaching method used in the control group led the students to a 'synthesis' model. In addition, the learning that occurred in the group taught with the HOMs was found to be more permanent than the learning that occurred in the control group. Based on these results, the use of HOMs to teach astronomy and the generalisation of these models has been recommended. Lastly, issues to consider when teaching the subject of seasons have been outlined.